CREATIVE DIGITAL OFFICE: DIGITAL ECONOMY OFFICE IN SOUTH JAKARTA - Soaduon Abraham, Ario
Indonesia is a country with the highest digital economy value and growth in Southeast Asia. This is a great potential for Indonesia’s economy in the future, coupled with the fact that the digital economy is also the key to economic recovery post COVID-19. However, the reality is that digital economic growth in Indonesia is still fragmented, therefore, inclusive digital economy facilities are needed so that digital economic growth in Indonesia goes optimally. This project is a fictitious project owned by a private company that wants to build a digital economy facility in South Jakarta. The land occupied by this project is 7000 m2 and the total floor area is 21000 m2. The building consists of 2, 6 floor high building masses that are connected by a ‘bridge’ mass to support the building design concept. The study of generation Z workforce and the activities that need to be supported in a digital technology office form the basis of the space concept and requirements. This building houses several functions, including a main office, rental office, coworking space, and communal space. Design issues are then reduced into space quality requirements. Creative Workspace and Engaging Design issues are answered with spaces that are interactive, visible, flexible, and full of activities. From the space quality, the main concept of "Machine of Interactions" was formed, it is where the building encourages interaction between users, both workers and visitors, to create a work environment that encourages innovation and new ideas. The uniqueness of this project comes from how this building attempts to reimagine an office building that focuses on creating an optimal environment for digital economy to grow. The space requirements and the quality of the space give shape to the building and create a new and unique forms for this project.